IMPLEMENTATION OF GOVERNMENT DECENTRALIZATION IN REALIZING VILLAGE AUTONOMY BASED ON LAW NUMBER 3 OF 2024 CONCERNING VILLAGES - Khasanofa, Auliya; Subur, Subur (NOMOI Law Review, 2024)
Decentralization policy is a process of government devolution to the people. The implementation of decentralization in realizing village autonomy based on community development and development makes the village government competent. In March 2023, urban poverty data reached 7.29 percent and rural areas 12.22 percent, meaning that to grow village autonomy requires a growth budget. So in Article 9 paragraph (1) of Law No. 19 of 2023 concerning the 2024 State Budget, the TKD costs in 2024 are planned at IDR 85.6 trillion. And paragraph (2) letter f that from the TKD figure, the village fund transfer is 71,000.0 trillion. This study is to explain the role of the government in the decentralization of village autonomy with the presence of Law No. 3 of 2024 concerning Villages, in addition to village funds where the term of office of the village head is increased to eight years. The people who are one of the factors driving economic growth can be competent in terms of effective resource management from development through the village government. The method used in this research is a normative juridical legal research method with the approach used is a qualitative descriptive approach. The results of this discussion, with the birth of the law, have opened up opportunities for villages to manage village finances for priority programs. Village funds issued by the government can be used as village community development and village government socialization of village funds for education, health, and social security. However, in the implementation of village autonomy, the community has not had an active role in its management. Therefore, the village government must be more transparent about village funds and capable of taking an important role for golden Indonesia.